2009
DOI: 10.1097/ccm.0b013e31819ffd5b
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a prognostic and diagnostic tool for septic complications after major trauma*

Abstract: PCT plasma reinduction marks possible septic complication during systemic inflammatory response syndrome after major trauma. In addition, high PCT concentration at admission after trauma in ICU patients indicates an increased risk of septic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 31 publications
4
77
1
2
Order By: Relevance
“…The mean values ranged from 4.3 (nonsevere sepsis) to 21.3 ng/mL (septic shock) (5,14,15) . In the present study, the median PCT values in patients with sepsis and trauma were similar to those found by Castelli et al (13) and Billeter et al (3) , respectively. Although the initial values of PCT in patients with sepsis are usually higher in more severe patients, the correlation with mortality is not as clear (5,14) .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The mean values ranged from 4.3 (nonsevere sepsis) to 21.3 ng/mL (septic shock) (5,14,15) . In the present study, the median PCT values in patients with sepsis and trauma were similar to those found by Castelli et al (13) and Billeter et al (3) , respectively. Although the initial values of PCT in patients with sepsis are usually higher in more severe patients, the correlation with mortality is not as clear (5,14) .…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were obtained by other researchers (12) . Castelli et al (13) also found that PCT values correlated with the severity and outcome of trauma. Moreover, in sepsis patients, particularly bacterial, initial PCT values proved to be far higher.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[22][23][24] In patients with a new onset of infection after a procedure, various laboratory parameters such as CRP and ESR level may be misleading as they are increased in all patients in the postoperative period and are not specific for underlying PCT as a predictor for infection after SCI surgery H Nie et al infection. 11 A trauma itself and the inflammatory reaction caused by the trauma surgery may stimulate the production of cytokine, leading to a nonspecific increase of these commonly used markers of inflammation. Thus, there is unmet need for specific markers of infection after surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Nevertheless, in current clinical practice, PCT are not widely used as routine screening tests in the early postoperative period, with most surgeons relying on the leukocyte count, CRP and ESR despite evidence that these are poor diagnostic tests. 9 PCT was already used in several other studies to predict postoperative infections after several different operations, [5][6][7][8]10,11 however, the predictive value of serum PCT in detecting postoperative infectious complications in spinal cord injury patients has not been studied.…”
Section: Introductionmentioning
confidence: 99%